Reviewing the compounding risks for tuberculosis drug-induced liver injury in a patient with transfusion dependent thalassaemia - Rofii, Nursafinas; Daut, Ummi Nadira; Lau, Su Yin (Universiti Putra Malaysia, 2023)
A patient presents with jaundice three weeks into commencement of anti-tuberculosis therapy (ATT). Tuberculosis drug-induced liver injury (TB-DILI) is a main concern in patients commencing ATT. Studies have reported various risk factors associated with TB-DILI, urging vigilance in monitoring liver enzymes in these patients. We aim to review the causes of jaundice in a patient with transfusion dependent thalassaemia commenced on ATT and highlight the risk factors associated with TB-DILI.